Patenting and strategies of major pharmaceutical companies in Brazil (Research, Society and Development, 2020)
Facing the contemporaneous changes which have intensified the market competition, survival strategies are essential for the company sustainability, such as the protection of intangible assets through the patents, which confer several advantages. In the pharmaceutical industry, where the products are result from expensive processes, the patents have become an important incentive. This article has undertaken a systematic analysis of patenting in the Brazilian pharmaceutical industry, evaluating the patents indicators of the major pharmaceutical companies in Brazil in order to categorize their strategies. The results indicated the leadership of Aché in patent applications, an extremely small number of concessions, characterizing the majority of the deposits as Invention Patents, and the lack of partnerships with universities and /or foundations for research support. The EMS and Eurofarma companies have presented analytical strategic performance, the União Química, defender, and Aché and Hypermarcas, prospector performance.